The Karlamagnús Compendium: Genre and Meaning in AM 180a-b fol. - Williams, Harry, 1983- (2017)
This thesis is an examination of the fifteenth century manuscript AM 180a-b fol.; made up of a copy of the A version of Karlamagnús saga (180a) and seven further sagas - Konráðs saga keisarasonar, Dunstanus saga, Katrínar saga, Bærings saga, Knýtlinga saga, Vitus saga and Laurentius saga (180b), it originally formed one codex. The thesis has two main aims: to consider the generic position of Karlamagnús saga as it existed for the compilers of the manuscript and to speculate on the producers, purpose and use of the manuscript by means of a holistic consideration of its parts. The first aim is prompted by viewing the sagas of 180b as a reflection of the generic ambiguity of Karlamagnús saga. While patently belonging to the riddarasögur, Karlamagnús saga has affinities with hagiography and the konungasögur; representatives of these three generic classes are to be found in 180b. Structured by the theme of saintliness, in which a chronological line of saintly figures is presented, as well as shared geographical referents, the codex is marked by a wide-ranging intellectual curiosity. This is attributed to the concerns of the North Icelandic Benedictine School, the presence of which is marked in the manuscript, and to the wider intellectual atmosphere of fourteenth century Iceland in which saints' lives and romances were possibly written by the same people. Þessi ritgerð skoðar fimmtándu aldar handritið AM 180a-b fol.; sem samanstendur af A gerð Karlamagnúsar sögu (180a) ásamt sjö öðrum sögum- Konráðs sögu keisarasonar, Dunstanusar sögu, Katrínar sögu, Bærings sögu, Knýtlinga sögu, Vitus sögu og Laurentiusar sögu (180b), sem upphaflega mynduðu saman eitt handrit. Ritgerðin hefur tvö megin markmið: annars vegar að skoða í hvaða bókmenntaflokki Karlamagnúsar saga var álitin af þeim sem að settu saman handritið og hins vegar vangaveltur um hverjir það voru sem settu það saman, tilgangi þeirra með samsetningu þessara rita og hver notkun og hlutverk þessa handrits gæti hafa verið með því að horfa á það heildrænt. Hvatinn ...